An Early Experience of Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA) in the Republic of Korea: A Retrospective Multicenter Study - Joonhyeon Park; Sung Woo Jang; Byungchul Yu; Gil Jae Lee; Sung Wook Chang; Dong Hun Kim; Ye Rim Chang; Pil Young Jung (Journal of Trauma and Injury)
Purpose This retrospective multicenter study analyzed trauma patients who underwent resuscitative endovascular balloon occlusion of the aorta (REBOA) in the Republic of Korea. Methods This study was conducted from February 2017 to May 2018 at three regional trauma centers in the Republic of Korea. The patients were divided into two groups (cardiopulmonary resuscitation [CPR] and No-CPR) for comparative analysis based on two criteria (complication and mortality) for logistic regression analysis (LRA). Results There were significant differences between the CPR and No-CPR groups in mortality (p=0.003) and treatment administered (p=0.016). By LRA for complications, total occlusion has significantly lesser risk than intermittent or partial occlusion in both univariate (odds ratio [OR] 0.06, 95% confidence interval [CI] 0.00-0.36, p=0.01) and multivariate (OR 0.05, 95% CI 0.00-0.38, p=0.01) analyses. The Rescue had a higher risk than the Coda or Reliant in univariate analysis (OR 4.91, 95% CI 1.14-34.25, p=0.05); however, it was not statistically significant in multivariate analysis (OR 6.98, 95% CI 1.03-74.52, p=0.07). By LRA for mortality, the CPR group was the only variable that had a significantly higher risk of mortality than the No-CPR group in both univariate (OR 17.59, 95% CI 3.05-335.25, p=0.01), and multivariate (OR 24.92, 95% CI 3.77-520.51, p=0.01) analyses. Conclusions This study was conducted in the early stages of REBOA implementation in the Republic of Korea and showed conflicting results from studies conducted by multiple institutions. Therefore, additional research with more accumulated data is needed.